Produção de biodiesel via transesterificação do óleo de nabo forrageiro - Pedro Wallace de Paula Amaral do Valle (2009)
The obtainment of solid, liquid and gaseous fuels from biomass is among the well-known possibilities of the use of the energetic resources. Brazil is considered a privileged country to develop from biomass point of view, due to its vast farmland, abundance of water and high incidence of solar radiation on the land, and the availability of rural workforce. Pró-Álcool (Brazilian Alcohol Program), which was established in 1975, was a good example of the use of biomass for the production of energy. The current worldwide increasing interest in the production and use of biodiesel as an alternative for diesel seems to show a one way path towards the gradual substitution of petroleum. The search for technologies that maximize theconversion of vegetable oil in biodiesel using clean processes has been the goal of research carried out worldwide, and the work presented herein is an initiative in that direction. In all these studies, optimum synthesis conditions were established by means of chemometric techniques of experimental design, using Response Surface Methodology RSM. This work carries out a large research on the use of fodder radish crude oil (Raphanus sativus L. var. oleiferus Stokes) as a row material for biodiesel synthesis, using ethanol as well as methanol as reagents in the process. Two synthesis were studies: the classical process (catalyzed by base) and the supercritical process (without a catalyst). The use of hydrated ethanol (92,8INPM) and soybean refined oil in the supercritical synthesis were also studied The results obtained using the classical synthesis of biodiesel from fodder radish oil confirmed that the use of alkoxide catalysts allows the transesterification reaction to be carried out in a single step, with high and good efficiency, even in the cases where hydrated alcohol was used; scavenging water and chemical products were cut out from the final product purification stage of the reaction, which thus reduced to the distillation of surplus ethanol and to the separation of glycerin by decantation or centrifugation. The final conclusion of this work was that fodder radish and the supercritical processshould be considered interesting alternatives of raw material and process, respectively, to produce biodiesel.